PENTINGNYA PENDIDIKAN PERBANKAN UNTUK MENGATASI KELANGKAAN MODAL DALAM UMKM - Setiadi Umar (Bina Ekonomi, 2010)
According  to the Ministry of Trade and Industry of the Republic of Indonesia (Deperindag), there are problems  faced by Small Medium Enterprise(s) (SMEs)  to develop themselves. Some of these problems are  the  insufficiency  capital,  limited knowledge,  uncompetitive  financing schemes and  lack of education  of the SME's owners aggravating  the problem. This paper discusses  the condition of Indonesian banking and other financial  institutions as well as capital  conditions,  the condition of SME(s,) and the needs of financial and business education  for SMEs. Finally, this paper suggests  alternative  solutions to the problem.Keywords: Small Medium Enterprises (SME)s, SMEs development, SMEs Business Education, Indonesian  Banks and LDR, private sector development.